GE_GERICHTE C/14765/2013 vom 12. September 2014 - GE Cour de justice (2014)
RECONNAISSANCE DE LA DÉCISION; MAINLEVÉE DÉFINITIVE; RÉSERVE DE L'ORDRE PUBLIC; DOMICILE | LDIP.29; LDIP.25; LDIP.20; LDIP.26.A; CPC.326.1; CPC.126.1; LDIP.27; RTFMC.26; RTFMC.88; RTFMC.89